Providing a lean and agile supply chain model in project-based organizations - Mohammadreza Zahedi; Morteza Abbasi; Shayan Naghdi Khanachah (Annals of Management and Organization Research)
Purpose: One of the differences between project-oriented and routine organizations is the difference in their supply chain. This leads to the use of distinct and new approaches to its management. In this article, according to the existing problems, a conceptual model of lean and agile supply chain in project-oriented organizations is presented by examining the lean functions and agility of supply chain discussion. Research methodology: This research is descriptive-analytical in terms of method and applied in terms of purpose. This study's statistical population includes all managers and supply chain experts of project-based organizations and the statistical sample includes 105 people who have been selected using a purposive sampling method. After presenting the conceptual model, a researcher-made questionnaire was used to collect information and to examine the intended model, the structural equation approach with PLS software was used. Results: The research findings indicate that the 114 identified items for the research model significantly explain their related components. The results of the model fit study showed that based on the convergent validity indices, Cronbach's alpha and Cronbach's alpha, and the subscription validity index and the exponential or redundancy validity index, the model is in the desired condition. Limitation: This research only described Knowledge Based Centre. Contribution: Organizations realised that relying on existing knowledge alone was not enough to compete in a competitive environment, and went beyond the boundaries of their organization to acquire knowledge. Organizations considered customers as a very useful and knowledgeable resource, and activities should be done to interact with customers in leading organizations. Keywords: Customer assisted knowledge production capacity, Customer capital, Intellectual capital, Knowledge management